Factors Affecting Presentation and Treatment of Pediatric/Adolescent Cancer Patients Diagnosed With SARS-CoV-2. Issue 3 (3rd February 2023) - Sharma, Ishna; Hamby, Tyler; Noorani, Sahil; Liu, Angela; Omar, Salma; Ahmad, Hufsa; Watts, Shelley; Hoeft, Alice; Whitworth, Suzanne; Ray, Anish
Abstract : Background: It is thought that the clinical course of actively treated pediatric/adolescent cancer patients diagnosed with severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) is more severe than experienced by the general pediatric population. We describe the clinical course, risk factors affecting presentation, and management of coronavirus disease 2019 (COVID-19) infection for these patients. Methods: Patients at a single institution receiving cancer therapy while diagnosed with SARS-CoV-2 between January 2020 and June 2021 were retrospectively reviewed. Data collected included age at SARS-CoV-2 diagnosis, sex, ethno-race, adjusted body mass index, and active therapies. Results: Twenty-nine patients met inclusion criteria, with 16 (55.2%) experiencing symptoms. Twenty-three (79.3%) patients required no institutional support; 10 (34.4%) required hospitalization, of which 80.0% required oxygen, 30.0% required intensive care, and 10.0% required intubation. Three (10.3%) patients developed MIS-C. Obesity increased odds of hospitalization (odds ratio=25.5; P =0.002) and oxygenation (odds ratio=14.88; P =0.012). Conclusions: Hospitalization and MIS-C rates were significantly higher than, whereas mortality rates and symptom presentations were consistent with, rates in the general pediatric population. Obesity was the only risk factor predictive of clinical severity. Cancer treatment modifications and pre-emptive administration of COVID-19 treatment did not modify clinical course.